Broadband acoustic energy confinement in hierarchical sonic crystals composed of rotated square inclusions - Shakouri, Amir (2018)
The propagation of acoustic waves in hierarchical sonic crystals is studied computationally and experimentally. These sonic crystals are composed of a hierarchical order of square inclusions rotated 45° with respect to the square lattice structure. It is shown that these hierarchical sonic crystals are capable of confining acoustic energy over a broad frequency range and at multiple lattice points inside the sonic crystal based on Bragg's scattering effect. Fused deposition modeling additive manufacturing is applied to prepare a finite-sized sample of the hierarchical sonic crystal. Acoustic measurements are conducted on the hierarchical sonic crystal sample in a direct and closely plane-wave field inside an anechoic room. The experimental measurements are in good agreement with the band structure calculated using the finite element method. Potential applications of the hierarchical sonic crystals for acoustic energy harvesting and noise measurements are discussed.